Contemporary Translation Studies 2021
DOI: 10.46679/978819484830107
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Interpreting Teachers’ Use and Perceptions of Distance Interpreter Training (DIT) Before and After the COVID-19 Pandemic: An Interview-Based Study

Abstract: The study indicates that before the COVID-19 pandemic, despite its importance, distance interpreter training (DIT) was not positively perceived or widely used in higher education institutions that offer Bachelor of Translation and Interpreting (BTI) and/or Master of Translation and Interpreting (MTI) programs in China. However, the pandemic has changed almost everything in the world, with no exception of DIT, prompting the authors to have a follow-up study in August 2020 of the same 14 full-time interpreting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In accordance with findings from the research conducted by Mehrvaz and his colleagues, informal learning implemented online could be positive for improving students’ digital literacy and academic performance [ 33 ]. The endeavor to employ blended learning by resorting to online learning resources during the study was favored by participants in a similar fashion to the research of Xu et al [ 21 ]. In the present study, participants reported gains in both core competencies for interpreters (e.g., language abilities and interpreting-specific skills) and digital literacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with findings from the research conducted by Mehrvaz and his colleagues, informal learning implemented online could be positive for improving students’ digital literacy and academic performance [ 33 ]. The endeavor to employ blended learning by resorting to online learning resources during the study was favored by participants in a similar fashion to the research of Xu et al [ 21 ]. In the present study, participants reported gains in both core competencies for interpreters (e.g., language abilities and interpreting-specific skills) and digital literacy.…”
Section: Discussionmentioning
confidence: 99%
“…In China, where officially accredited T&I education were provided as part of the bachelor’s and master’s degree programs, experiences were gained from attempts to conduct ERT for trainee students from hundreds of universities. In a comparative study on the perceptions towards DIT in several universities across China, most respondents agreed that the pandemic and resulting changes in the training of interpreters promoted the development of online and blending approaches for interpreter training [ 21 ]. Contrarily, in a survey for students’ preferences for face-to-face mode versus distance learning mode of interpreter training, opinions and attitudes of students suggested that remote learning were still underappreciated due to limitations in the delivery approaches, learning environment and effectiveness [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In China, where officially accredited T&I education were provided as part of the bachelor's and master's degree programs, experiences were gained from attempts to conduct ERT for trainee students from hundreds of universities. In a comparative study on the perceptions towards DIT in several universities across China, most respondents agreed that the pandemic and resulting changes in the training of interpreters promoted the development of online and blending approaches for interpreting education (Xu, Zhao, and Deng 2021). Contrarily, in a survey for students' preferences for face-to-face mode versus distance learning mode of interpreting education, opinions and attitudes of students suggested that remote learning were still underappreciated due to limitations in the delivery approaches, learning environment and effectiveness (Zhiyao 2021).…”
Section: Interpreting Training In Covid-19mentioning
confidence: 99%